2019
DOI: 10.1097/mnm.0000000000000928
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of 18F-FDG PET/CT imaging in suspected recurrence of male breast cancer

Abstract: PurposeMale breast cancer (MBC) is a rare malignancy, with recurrence being one of the main adverse predictors for prognosis. The aim of the study was to evaluate the diagnostic and predictive value of fluorine-18-fluorodeoxyglucose (18F-FDG) PET/CT in the setting of suspected recurrence of MBC.Patients and methodsRetrospective analysis of PET/CT findings was performed in 23 previously treated, histologically proven patients with MBC (mean age: 59.3±10.9 years; range: 36–79 years) with suspected recurrence. Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Many studies also underlined the ability of 18 F-FDG PET/CT to reveal synchronous malignancies both at stage or restage evaluation. In particular, incidental lymphoma, prostate cancer, colon cancer, tongue cancer, esophageal cancer and thyroid cancer are the most frequent findings reported in literature [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies also underlined the ability of 18 F-FDG PET/CT to reveal synchronous malignancies both at stage or restage evaluation. In particular, incidental lymphoma, prostate cancer, colon cancer, tongue cancer, esophageal cancer and thyroid cancer are the most frequent findings reported in literature [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 3178 articles were extrapolated with a computer literature search by reviewing the titles and abstracts; 3171 of them were excluded because the reported data were not within the field of interest of this review. Seven articles regarding MBC were selected and retrieved in the full-text version [16][17][18][19][20][21][22]; furthermore, all the studies were again screened to find articles regarding breast cancer in general (with both male and female patients) with at least 10 male participants and one additional article was found [23]. No additional studies were found on screening the references of the aforementioned articles (Fig.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 37% of patients with clinical stage IIA-IIIC breast cancer who underwent F18-FDG PET/CT before preoperative systemic therapy showed more extensive disease, including 23% with more extensive nodal metastasis and 14% with distant metastasis [ 5 ]. The male breast cancer represents only 1% of all breast cancers [ 3 , 6 ] and the literature is by far less consistent than in women, studies have limited number of subjects and many are case reports [ 6 , 7 , 8 , 9 , 10 , 11 ]. In a recent study published by Ulaner et al [ 7 ] it is underlined that the role of F18-FDG PET/CT is based on female guidelines and that an analysis of the value of F18-FDG PET/CT for systemic staging of male breast cancer is warranted.…”
Section: Introductionmentioning
confidence: 99%